Malware data collection and analysis - Low, Song Chuan. (2013)
Malicious software, referred to as malware, is one of the main threats on the Internet in the present day. Millions of hosts on the Internet are infected with malware, ranging from classic computer viruses to Internet worms and bot networks. A huge increase in the number of malware samples are collected by anti-virus vendors.